Pengaruh Sistem Pengendalian Internal Dan Akuntabilitas Terhadap Pengelolaan Penyaluran Dana Hibah - Khodijah Ishak; Siti Amalia (JAS (Jurnal Akuntansi Syariah), 2020)
This research was conducted to determine the effect of the internal control system and accountability on the management of the distribution of grant funds in the organizational unit of Bengkalis Regency. The type of data from this research is quantitative and the source of the data comes from primary data. Data collection used in this research is data in the form of a questionnaire distributed to 22 Organizations of Related Regional Organizations and sampling using purposive sampling techniques. Data analysis techniques using multiple linear regression test. The results of this research are partially and simultaneously the internal control system and accountability significantly influence the management of the distribution of grant funds, the magnitude of the influence of the internal control system and accountability of 81.6% and 18.4% are influenced by other factors.